Perancangan dan Implementasi Frontend Website Company Profil untuk PT. Sarana Bangun Sejati - Dedy Susanto; Syaeful Anas Aklani; Mangapul Siahaan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
This study aims to design and implement the front end of a company profile website for PT Sarana Bangun Sejati as a digital platform to enhance its corporate image and business communication in the digital era. The development process involved needs analysis, user interface design using HTML, CSS with the Bootstrap 5 framework, JavaScript, and PHP, and applied the Agile Scrum methodology consisting of three weekly sprints. The website is designed to be responsive and compatible across various devices, with a page structure that includes Home, About Us, Products, Projects, Gallery, and Contact. The final outcome of this project is a fully functional website that serves as an official digital communication and promotional medium, supporting the company's online presence and enhancing public trust.